Wu-Tou Decoction in Rheumatoid Arthritis: Integrating Network Pharmacology and In Vivo Pharmacological Evaluation - Guo, Qingqing; Zheng, Kang; Fan, Danping; Zhao, Yukun; Li, Li; Bian, Yanqin; Qiu, Xuemei; Liu, Xue; Zhang, Ge; Ma, Chaoying; He, Xiaojuan; Lu, Aiping (Frontiers in Pharmacology, 2017)
Purpose: This study aimed to explore underlying action mechanism of Wu-Tou Decoction (WTD) in rheumatoid arthritis (RA) through network pharmacology prediction and experimental verification. Methods: Chemical compounds and human target proteins of WTD as well as RA-related human genes were obtained from TCM Database @ Taiwan, PubChem and GenBank, respectively. Subsequently, molecular networks and canonical pathways presumably involved in the treatment of WTD on RA were generated by ingenuity pathway analysis (IPA) software. Furthermore, experimental validation was carried out with MIP-1β-induced U937 cell model and collagen induced arthritis (CIA) rat model. Results: CCR5 signaling pathway in macrophages was shown to be the top one shared signaling pathway associated with both cell immune response and cytokine signaling. In addition, protein kinase C (PKC) δ and p38 in this pathway were treated as target proteins of WTD in RA. In vitro experiments indicated that WTD inhibited MIP-1-induced production of TNF-, MIP-1 and RANTES as well as phosphorylation of CCR5, PKC δ and p38 in U937 cells. WTD treatment maintained the inhibitory effects on production of TNF- and RANTES in MIP-1β-induced U937 cells after CCR5 knockdown. In vivo experiments demonstrated that WTD ameliorated symptoms in CIA rats, decreased the levels of IL-1, IL-2, IL-6, TNF-, MIP-1, MIP-2, RANTES and IP-10 in serum of CIA rats, as well as mRNA levels of MIP-1, MIP-2, RANTES and IP-10 in ankle joints of CIA rats. Furthermore, WTD also lowered the phosphorylation levels of CCR5, PKC δ and p38 in both ankle joints and macrophages in ankle joints from CIA rats. Conclusions: It was demonstrated in this research that WTD played a role in inhibiting inflammatory response in RA which was closely connected with the modulation effect of WTD on CCR5 signaling pathway in macrophages.